The Routledge international handbook of existential human science
1 online resource.
Keywords: "This volume is the first handbook to explore existentialism as epistemology and method. Trans-disciplinary in scope, it considers the nature of human subjectivity and how human experience ought to be studied, examining the connections that exist between the individual's imagining of the world and their everyday practice within it. With attention to the question of whether humans are ultimately alone in their self-knowledge or whether what they know of themselves in constructed in common with others, it enables the reader to recognise core questions that frame the methods and orientation of an existential inquiry. In addition to historical exposition, it offers a variety of chapters from around the world that explore the diverse global spaces for, and different types of, existential focus and discussion, thus questioning the view that the existential 'problem' may be singularly a matter for the post-enlightenment West. The fullest and most comprehensive survey to date of what human beings can and should make of themselves, The Routledge International Handbook of Existential Human Science will appeal to scholars across the humanities and social sciences with interests in anthropology, sociology, philosophy and research methods"--